Transnational peasants : migrations, networks, and ethnicity in Andean Ecuador - Kyle, David, 1960- (Johns Hopkins University Press, 2000)
One of the hallmarks of contemporary international migration is not simply its scope but its geographic and ethnic diversity. Do new migrant groups follow the well-known patterns of past immigrations or do they forge new strategies? How well do existing theories of international migration fare in explaining new cases of transnational mobility? The first book on the variety of transnational migrations from Ecuador, Transnational Peasants provides an intriguing historical and sociological exploration of a contemporary migration mystery: Why do two groups from the same country pursue radically different economic strategies of transnational mobility?David Kyle examines the lives of people from four rural communities in two regions of the Andean highlands of Ecuador. Migrants from the southern province of Azuay shuttle back and forth to New York City, mostly as undocumented laborers. In contrast, an indigenous group of Quichua-speakers from the northern canton of Otavalo travel the world as handicraft merchants and musicians playing Andean music. In one village, Kyle found that Otavalans were migrating to 23 different countries and returning within a year.Kyle rejects the notion that contemporary globalization through technology is the primary cause of this mobility. He argues that patterns of transnationalism, developed over several centuries and varying by region and ethnicity, continue to play a crucial role in who will leave Ecuador and who will stay. Yet migrants' use of professional "migration merchants", including smugglers, leads to a phenomenon that transcends the original sending conditions of the 1980s; even cash-poor rural small-holders in communities lacking telephone service can buy a clandestine passage to Manhattan.